Efficacy of Counseling Cognitive Behavior Groups to Enhance Students Self-Esteem Social Media User - Pernama, Ayu; Wibowo, Mungin Eddy; Mulawarman, Mulawarman (Jurnal Bimbingan Konseling, 2019)
The purpose of this study is to test and analyze the behavioral group counseling behavior of the self-instruction techniques to increase the self-cost of students of social media users. This study used the experimental method of pre-test and multiple post-test group design were involved 7 students of class VIII at SMPN 13 Semarang. The Data collection uses statistical self-esteem inventory (SEI). The data analysis in this study used repeated ANOVA measurements. The results of this study are to encourage the levels of student performance before and after being given a self-instruction technique counseling group. The results of the research conducted were cognitive behavioral group counseling, effective self-instruction techniques to improve the self-efficacy of students of social media users.